A multigroup analysis of family climate and volunteering: The mediating role of parental conversations in emerging adulthood. Issue 2 (3rd April 2022) - Gonul, Buse; Işık, Hatice; Güneş, Seren
Abstract: The current study aims to examine the predictive role of family climate (relatedness in family, cognitive cohesion, and intergenerational authority) in volunteering through conversations with parents in emerging adulthood while also considering the effects of gender. A total of 507 emerging adults reported their participation in volunteering, perceptions of family climate, and frequency of conversations with their parents about volunteering. Results of the structural equation modeling showed that even though relatedness in family and cognitive cohesion predicted emerging adults' volunteering, the mediating roles of parental conversations with mothers and fathers differed based on family climate domains. Intergenerational authority did not yield any significant effects. Multigroup analysis revealed that participants' gender did not affect these family processes. The findings implied that a positive family climate was indirectly influential in promoting emerging adults' participation in volunteering by providing them an open environment to share their views on societal issues.